Pengaruh Kecerdasan Emosional terhadap Manajemen Konflik dimediasi oleh Komunikasi Interpersonal (Studi pada Mahasiswa Program Studi Manajemen, Fakultas Ekonomi & Bisnis Universitas Nusa Nipa) - Martina Rudolfa Da Mendez; Yuliana Onang (Jurnal Projemen UNIPA, 2025)
This study investigates the effect of emotional intelligence on conflict management with interpersonal communication as a mediating variable. The research was conducted on students of the Management Study Program, Faculty of Economics and Business, Universitas Nusa Nipa, who attended the Conflict and Negotiation Management course during the even semester of the 2024/2025 academic year. A quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the relationships among variables. The results show that emotional intelligence significantly influences interpersonal communication. Interpersonal communication, in turn, significantly influences conflict management. However, the direct effect of emotional intelligence on conflict management was not significant. Mediation analysis reveals that interpersonal communication significantly mediates the relationship between emotional intelligence and conflict management. These findings highlight the importance of communication skills in translating emotional capacity into effective conflict resolution strategies. Practically, the study recommends that emotional intelligence training be accompanied by structured development of interpersonal communication skills in university curricula.